Diagnosing Norms Surrounding Sexual Harassment at a Jordanian University - Bergenfeld, Irina; Cislaghi, Beniamino; Yount, Kathryn M.; Essaid, Aida A.; Sajdi, Jude; Taleb, Rand Abu; Morrow, Grace L.; D’Souza, Janice S.; Spencer, Rachael A.; Clark, Cari Jo (Frontiers in Sociology, 2021)
Sexual harassment (SH) is a form of gender-based violence (GBV) that negatively impacts women’s physical, mental, social, and financial well-being. Although SH is a global phenomenon, it also is a contextualized one, with local and institutional norms influencing the ways in which harassment behavior manifests. As more women attend institutions of higher education in Jordan, these women are at increased risk of experiencing SH in university settings, with potential implications for their health and future employment. Social norms theory, which examines the informal rules governing individual behavior within groups, has been a useful framework for understanding and developing interventions against GBV globally. We sought to apply a social-norms lens to the understanding and prevention of SH at a Jordanian university. To gain a comprehensive and nuanced picture of social norms surrounding SH, we collected qualitative data using three complementary methods: focus group discussions (n = 6) with male and female students (n = 33); key informant interviews with staff and faculty (n = 5); and a public, participatory event to elicit anonymous short responses from students (n = 317). Using this data, we created a codebook incorporating social-norms components and emergent themes. As perceived by participants, SH was unacceptable yet common, characterized as a weak norm primarily because negative sanctioning of harassers was unlikely. Distal norms related to gender and tribal affiliation served to weaken further norms against SH by blaming the victim, preventing reporting, discouraging bystander intervention, and/or protecting the perpetrator. The complexity of the normative environment surrounding SH perpetration will necessitate the use of targeted, parallel approaches to change harmful norms. Strengthening weak norms against SH will require increasing the likelihood of sanctions, by revising university policies and procedures to increase accountability, increasing the acceptability of bystander intervention and reporting, and fostering tribal investment in sanctioning members who harass women. Creating dialogue that emphasizes the harmful nature of SH behaviors and safe spaces to practice positive masculinity also may be an effective strategy to change how male students interact in the presence of peers. Any social norms change intervention will need to consider the various reference groups that dictate and enforce norms surrounding SH.